Ketamine metabolite (2R, 6R)-hydroxynorketamine enhances aggression via periaqueductal gray glutamatergic transmission. (October 2019) - Ye, Lichao; Ko, Chih-Yuan; Huang, Yuting; Zheng, Chen; Zheng, Yanfang; Chou, Dylan
Abstract: (2 R, 6 R )-hydroxynorketamine (HNK), a metabolite of ketamine, has recently been suggested to be a potent antidepressant for treating animal depression and has rapid-onset and long-lasting action through potentiating glutamatergic transmission. However, its other effects are still unclear. In the present study, we tested the effects of (2 R, 6 R )-HNK on offensive aggression. A resident-intruder (RI) test was used as the main model to test elements of offensive aggression, including threats and bites. Electrophysiological recordings in the ventrolateral periaqueductal gray (vlPAG) were used to measure the functions of glutamatergic synaptic transmission. A single systemic injection of (2 R, 6 R )-HNK, but not (2 S, 6 S )–HNK, increased elements of offensive aggression, including threats and bites, in a dose-dependent manner with long-lasting action. Moreover, (2 R, 6 R )-HNK increased the input-output curve, the AMPA-mediated current, and the frequency and amplitude of miniature excitatory postsynaptic currents (mEPSCs) and decreased the paired-pulse ratio (PPR) in the vlPAG. Furthermore, intra-vlPAG application of (2 R, 6 R )-HNK increased aggressive and biting behaviors, which were abolished by an intra-vlPAG pretreatment with the AMPA receptors antagonist, CNQX. Notably, the intra-vlPAG CNQX pretreatment eliminated systemic (2 R, 6 R )-HNK-enhanced aggressive and biting behaviors. The results of this suggest that (2 R, 6 R )-HNK evokes offensive aggression by increasing vlPAG glutamatergic transmission. Although (2 R, 6 R )-HNK is currently suggested to be effective for treating depression, its side effect of increasing offensive aggression should be a subject of concern in future drug development and therapy. Highlights: ( 2 R, 6 R )-hydroxynorketamine increases aggressive behaviors. ( 2 R, 6 R )-hydroxynorketamine potentiates AMPA receptor-dependent synaptic transmission in the vlPAG. VlPAG glutamatergic transmission contributes to( 2 R, 6 R )-hydroxynorketamine-enhanced aggressive behaviors.